HUBUNGAN PENGETAHUAN DENGAN CAKUPAN K4 PADA IBU HAMIL DI PUSKESMAS SANGKUNUR - Lena Juliana Harahap (Poltekkes Kemenkes Medan, 2021)
Antenatal Care (ANC) is a planned program in the form of observation, education and medical treatment for pregnant women to obtain a safe and satisfying process of pregnancy and childbirth. ANC visits should be done at least 4 times during pregnancy, namely K1 to K4, with a time distribution of at least 1 time in the first trimester (0-12 weeks of gestation), at least 1 time in the second trimester (12-24 weeks of gestation), and at least 2 times in the third trimester (24 weeks gestation - birth). This type of research is an analytic study with a cross sectional design. The population in this study were all 124 pregnant women in the final third semester of Sangkunur Health Center using simple random sampling of 95 people. Data obtained from the Sangkunur Health Center and through the results of interviews using a questionnaire. The data analysis method was analyzed by univariate, bivariate using the Chi-square test. Based on the results of statistical tests with the Chi-square test, it is known that there is a relationship between knowledge and K4 coverage in pregnant women (0.006 <0.05). It is recommended to Sangkunur Health Center to regularly provide outreach to pregnant women about the importance of conducting antenatal care visits in order to get antenatal care services so that pregnant women can visit health service places.